Diagnosing the zone of tolerance for hotel services - Nadiri, Halil; Hussain, K. K. (My University, 2005)
Purpose - Aims to address the concept of the "zone of tolerance" in judgments of hotel service quality. The present study describes the zone of tolerance for customers' service expectations and determines the customer satisfaction level in Northern Cyprus hotels - which is a new emerging market as an island destination. Design/methodology/approach - The sample of the study consisted of customers visiting four-star, five-star, and resort hotels located in the Gazimagusa and Kyrenia regions of Northern Cyprus in June and July 2004. The questionnaire was based on service expectations and perceptions. As a result of the pilot study with 50 customers, the instrument was reworded for measuring service quality and the zone of tolerance for hotels. This modified instrument became the "HOTELZOT" instrument, which was used to measure customers' service expectations and service perceptions. Psychometric properties of the scale (such as reliability) were tested, and the dimensionality of the scale was confirmed through an exploratory factor analysis. Findings - The conceptual model (HOTELZOT) presented here, and the results of this study, demonstrate that evaluation of services can be scaled according to different types of expectations - "desired" and "adequate" - and that customers use these two types of expectations as a comparison standard in evaluating hotel services. The findings reveal that the customers visiting Northern Cyprus hotels have a narrow zone of tolerance in services provided by the hotels. The results also indicate that the HOTELZOT instrument presented here is two-dimensional. The results with respect to gap analysis reveal that there was a shortfall in the service quality provided by the hotels in the sample, with the largest gap being found in intangibles. Research limitations/implications - First, the sample in this study is small and is limited to a relatively specific group of tourists. Second, measurement of customer satisfaction was carried out using a single-item scale, and it was therefore not possible to estimate its reliability. Finally, this study examined the influence of two factors on customers' zones of tolerance for hotels. As proposed by Zeithaml et al., there might be other factors that determine the width of the zone of tolerance. Originality/value - This study is necessary, useful, and relevant because: It focuses on service quality in island destinations (which have received little attention in the past); Northern Cyprus is both an island and a virgin market in the Mediterranean where quality of hotels is a significant strategic issue for increasing the competitiveness in the international tourism market; and the study explores service quality in terms of the zone of tolerance in the hospitality industry. © Emerald Group Publishing Limited.
Keywords: Customer satisfaction; Cyprus; Hotels; Service quality assurance; Tolerances